Pengaruh Trust Terhadap Keputusan Beli Produk Tiff Body - Yohana Nadya Gunardja (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The shift of the Indonesian lifestyle has become online oriented has a huge impact on e-commerce business's popularity. This study aims to determine the influence of trust on to purchase decision of Tiff Body's product. This research uses the quantitative methodology and data collection method to use an online questionnaire with a purposive sampling technique distributed to 100 respondents who have been shopping at Tiff Body. After the data is analyzed using Simple Linear Regression with IBM SPSS Statistics 25 program, the result shows that trust influences purchase decisions.